The behaviour of tilapia (Oreochromis mossambicus) in an environment contaminated with detergent powder (Alkyl Benzene Sulphonate) - Samaruddin, Muhammad Kadri; Khairunnisa, Nabilah Fathimah; Kurnia, Eva; Widarto, Tri Heru (Universitas Malikussaleh, 2025)
Water pollution due to detergents can have an impact on changes in the activity of aquatic organisms including tilapia. tilapia. This study aims to determine the impact of concentration and duration of exposure to detergents on the behaviour of tilapia fish (Oreochromis mossambicus). This study used experimental method laboratory experimental method with five treatments of concentration of 0 ppm, 1.6 ppm, 3.2 ppm, 4.8 ppm, and 6.4 ppm and three replications for each treatment. Observations of mortality rate, behaviour, and environmental parameters were conducted every 24 hours. The results showed that the LC50 value of Alkyl Benzene Sulfonate at 72 hours exposure was 6.4 ppm. Surfactant exposure affected water quality by lower DO values, but had no effect on temperature, pH, and salinity. The most observed behaviours were swimming in place and bottom swimming. The results of the Kruskal-Wallis test showed a p-value > 0.05 so there was no effect between the concentration and time of exposure to detergent on surface swimming and feeding behaviour. In contrast, the effect of concentration and time of exposure to detergent was seen on operculum opening, as evidenced by the ANOVA test results with p-value < 0.05 and F > F crit. Tukey's further test showed significance between concentrations of 6.4 - 1.6 ppm, 6.4 - 3.2 ppm, and 0 - 6.4 ppm with p-value < 0.05.Keywords: Alkyl Benzene Sulfonate, Tilapia Fish, Mortality, Fish Behaviour